Związek Bojowników o Wolność i Demokrację na Warmii i Mazurach w latach 1947-1975. Zarys dziejów - Korejwo, Mariusz (Komunizm: System - Ludzie - Dokumentacja, 2015)
Society of Fighters for Freedom and Democracy was formed in 1949 as a merger of almost all previously existing veterans’ associations. At the regional level, the most important element of the Association was the regional board and the superordinate bodies were poviate boards and clubs. Within the Regional Board there were merit-based commissions (e.g. verification, propaganda, health, medals, social), and after 1956 - also the so-called social group commissions (e.g. political prisoners, participants of revolution fights, fighters for the independence of Warmia and Mazury). In the years 1949-1956, the Association was in fact only a tool of political indoctrination and was strictly governed by political authorities that aimed at liquidating the Association. After 1956, the Association became totally independent and the veterans were given a limited possibility of postulating, mainly in social matters. The condition for being a member of the Association was loyalty towards the communist state.